Implementation of a web-based data archival management system - Mkpojiogu E.O.C.; Efeakusu G.; Hussain A.; Hashim W. (Science and Engineering Research Support Society, 2023)
This study reports on the implementation of a web-based data archival management system. Informed and vital decisions are made on the basis of the information that is available to either individuals or organizations. Since information is important, it is needful to achieve and manage them properly for ease of their retrieval when needed. Nonetheless, the sorting, storing, searching, retrieving and moving of files has hitherto been done manually and with papers which is inefficient, tedious, and time-consuming. This research implements a data archival and management system in Veritas University, Abuja which solves the challenges and complexities in the manual system of archiving and managing of information in the institution. 2020 SERSC.